Thermally conductive paste, semiconductor device and method for manufacturing semiconductor device

The thermally conductive paste, with its unique composition and curing process, addresses the adhesion and thermal conductivity issues in semiconductor packages, achieving strong adhesion and high thermal conductivity for improved semiconductor device performance.

JP2025059814APending Publication Date: 2025-04-10SUMITOMO BAKELITE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170135
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing thermally conductive layers in semiconductor packages face challenges in achieving strong adhesion over large bonding areas, which affects the thermal conductivity and reliability of the semiconductor devices.

Method used

A thermally conductive paste is developed, comprising particles, thermosetting resins, and solvents with a metal-coated surface, which is cured under specific conditions to achieve an adhesion strength of 310N or more and a thermal conductivity of 12W/m·K or more.

Benefits of technology

The thermally conductive paste provides excellent adhesion and thermal conductivity, effectively addressing the adhesion challenges in large area bonding and enhancing the heat dissipation characteristics of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059814000001_ABST
    Figure 2025059814000001_ABST
Patent Text Reader

Abstract

To provide a thermally conductive paste, a semiconductor device, and a method for manufacturing the semiconductor device that realizes a thermally conductive layer with excellent adhesion in large-area bonding.SOLUTION: In a semiconductor device having a substrate 10, a semiconductor element 20, a heat spreader 30, a thermally conductive layer 40, a heat sink 50 and a thermally conductive layer 60, thermally conductive pastes used for bonding large areas of 2 cm2 or more contain particles that are at least partially metallic on the surface, thermosetting resin, and solvent, and the adhesion strength measured under specific conditions is 310 N or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive paste, a semiconductor device, and a method for manufacturing a semiconductor device. [Background technology]

[0002] In a semiconductor package having a thermal conductor, the use of a thermally conductive layer having a particle-connected structure formed by sintering metal particles by heat treatment is being considered. Patent Document 1 describes a semiconductor package having a substrate, a semiconductor element, a heat spreader, and a heat sink, in which the heat spreader and the heat sink are joined by a thermally conductive layer (thermal conductive material). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020 / 189446 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, the use of a thermally conductive layer to bond larger bonding surfaces has been considered. Based on this background, the inventors have found that there is room for improvement in the adhesion of the thermally conductive layer in large-area bonding. [Means for solving the problem]

[0005] According to the present invention, there are provided the following thermally conductive paste, semiconductor device, and method for manufacturing a semiconductor device. [1] 2cm 2 A thermally conductive paste used for bonding in the above area, The method includes the steps of: forming a particle having at least a portion of a surface thereof made of metal; forming a thermosetting resin; and forming a solvent; A thermally conductive paste having an adhesion strength of 310 N or more as measured under the following condition 1. [Condition 1] 1. Prepare a copper plate measuring 10 mm or more x 10 mm or more and an aluminum plate measuring 10 mm x 10 mm and 0.5 mm thick. 2.2mm 3 More than 5mm 3 The following thermally conductive paste is applied to the copper plate. 3. The aluminum plate is placed on the area of ​​the copper plate where the thermally conductive paste is applied, and the aluminum plate is pressed against the copper plate with a pressure of 50N or more and 100N or less. 4. The thermally conductive paste is hardened under the following conditions: heating temperature: 200°C, heating time: 120 minutes. 5. In accordance with JIS Z 3198-7, a load is applied using a die shear tester with a shear jig moving speed of 20 mm / min, and the maximum shear load is taken as the adhesion strength. [2] The thermal conductivity of the hardened body obtained by hardening the thermal conductive paste under the conditions of a heating temperature of 200°C and a heating time of 120 minutes is 12 W / m K or more. [1] The thermal conductive paste according to the present invention. [3] The cure shrinkage rate measured under the following condition 2 is 15% or less. The thermal conductive paste according to [1] or [2]. [Condition 2] The thermally conductive paste is applied onto a chip measuring 1.7 mm x 7 mm. 2. A 3 mm x 3 mm chip is mounted on the area where the thermally conductive paste is applied, and the thickness T1 of the thermally conductive paste at this time is measured. 3. The thermal conductive paste is cured by heating from 30°C to 200°C over 60 minutes, and then heated at 200°C for 120 minutes, and the thickness T2 of the cured thermal conductive paste is measured. 4. The value of {(T2-T1) / T1} x 100 is the curing shrinkage rate. [4] The content of the solvent is 5 parts by mass or less based on the entire thermal conductive paste. A thermally conductive paste according to any one of [1] to [3]. [5] The particles include resin particles and coated silver powder containing silver that covers the surfaces of the resin particles. A thermally conductive paste according to any one of [1] to [4]. [6] Further comprising an allyl ester resin, A thermally conductive paste according to any one of [1] to [5]. [7] Includes a heat spreader and a heat sink. A semiconductor device, wherein the heat spreader and the heat sink are bonded by the thermal conductive paste according to any one of [1] to [6]. [8] A method for manufacturing a semiconductor device, comprising: bonding a heat spreader and a heat sink using the thermally conductive paste according to any one of [1] to [6]. Effect of the Invention

[0006] According to the present invention, there is provided a thermally conductive paste that realizes a thermally conductive layer with excellent adhesiveness in large-area bonding. [Brief description of the drawings]

[0007] The above objects, as well as other objects, features and advantages, will become more apparent from the following preferred embodiments and the accompanying drawings.

[0008] [Figure 1] FIG. 1 is a schematic diagram of an example of a semiconductor device according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, the same components are given the same reference numerals and the description will be omitted as appropriate. In addition, the drawings are schematic diagrams and do not correspond to the actual dimensional ratio.

[0010] A schematic diagram of an example of a semiconductor device according to this embodiment is shown in Fig. 1. As shown in Fig. 1, the semiconductor device according to this embodiment includes a substrate 10, a semiconductor element 20, a heat spreader 30, a thermally conductive layer 40, a heat sink 50, and a thermally conductive layer 60. The semiconductor element 20 is provided on the substrate 10, the heat spreader 30 surrounds the periphery of the semiconductor element 20, and the thermally conductive layer 40 bonds the semiconductor element 20 and the heat spreader 30. The thermally conductive layer 60 also bonds the heat spreader 30 and the heat sink 50.

[0011] The semiconductor element 20 may be, for example, a logic chip or a memory chip, or may be an LSI chip in which a memory circuit and a logic circuit are combined. The semiconductor element 20 may be configured in a BGA type package.

[0012] The semiconductor element 20 is mounted on the substrate 10 and electrically connected to the substrate 10. The semiconductor element 20 may be flip-chip connected to the substrate 10. In this case, the semiconductor element 20 is solder-connected to the substrate 10 via solder balls 60. An underfill material 70 may be filled in the gap between the semiconductor element 20 and the substrate 10. As the underfill material 70, a known material may be used, but it may also be a sealing material or a die attach material.

[0013] The substrate 10 may be, for example, a printed circuit board. One or more semiconductor elements 20 may be mounted on one surface of the substrate 10. Furthermore, electronic components other than the semiconductor elements 20 or a heat source may be mounted on one surface of the substrate 10. Meanwhile, the other surface of the substrate 10 (the surface opposite to the one surface) may have a connection structure that allows connection to another substrate. The connection structure may be, for example, a solder ball, a pin connector, or the like.

[0014] The heat spreader 30 may be made of any material capable of dissipating heat from a heat generating body such as the semiconductor element 20, and may be made of, for example, a metal material. The metal material may be, for example, one or a combination of two or more materials selected from copper, aluminum, stainless steel, etc. The heat spreader 30 may have a highly thermally conductive material other than a metal material, and may contain, for example, graphite, etc., inside.

[0015] The heat spreader 30 may be formed of a single metal layer made of the above metal material, or may be formed of a laminated structure in which multiple layers are laminated. From the viewpoint of thermal conductivity, it is preferable that at least the surface of the heat spreader 30 that is bonded to the thermal conductive layer 40 has the above metal material exposed, but it may be plated with other metals. For example, the plating film can be formed of nickel, gold, an alloy containing these as main components, or a laminated film of these. This enhances the rust resistance of the heat spreader 30.

[0016] The shape of the heat spreader 30 is not particularly limited as long as it has a lid structure that covers the semiconductor element 20. For example, the heat spreader 30 may be configured as a housing having an opening on the surface facing the semiconductor element 20. In other words, when viewed in a cross-sectional view in the stacking direction of the semiconductor element 20 and the heat spreader 30, the heat spreader 30 may be configured in a substantially U-shape.

[0017] A part of the heat spreader 30 may be bonded to the substrate 10 via an adhesive. For example, the tip of the side wall of the heat spreader 30 may be bonded to one surface of the substrate 10 by an adhesive. Any known adhesive can be used.

[0018] The thermally conductive layer 40 is interposed between one surface of the semiconductor element 20 and the other surface of the heat spreader 30 facing the one surface, and bonds them together. The lower limit of the thermal conductivity of the thermally conductive layer 40 is, for example, 10 W / m·K or more, preferably 15 W / m·K or more, and more preferably 20 W / m·K or more. This can improve the heat dissipation characteristics of the semiconductor package 100. On the other hand, the upper limit of the thermal conductivity of the thermally conductive layer 40 may be, for example, 200 W / m·K or less, or 150 W / m·K or less. The thermal conductivity is obtained by measuring in the thickness direction at 25° C. using a laser flash method.

[0019] The heat sink 50 may be made of any material having excellent heat dissipation properties, and may be made of, for example, the same material as that used for the heat spreader 30. The heat sink 50 may have a plurality of fins.

[0020] The thermally conductive layer 60 is interposed between one surface of the heat spreader 30 and the surface of the heat sink 50 facing the one surface, and bonds them together. The lower limit of the thermal conductivity of the thermally conductive layer 60 is, for example, 10 W / m·K or more, preferably 15 W / m·K or more, and more preferably 20 W / m·K or more. This can improve the heat dissipation characteristics of the semiconductor package 100. On the other hand, the upper limit of the thermal conductivity of the thermally conductive layer 60 may be, for example, 200 W / m·K or less, or 150 W / m·K or less. The thermal conductivity is obtained in the same manner as described above.

[0021] Furthermore, when electrodes are provided on the upper and lower surfaces of the semiconductor element 20, conductive members such as lead frames may be connected to the upper and lower surfaces of the semiconductor element 20. In this case, the heat sink 50 and the thermally conductive layer 60 may be provided on the upper and lower surfaces of the semiconductor element 20, respectively.

[0022] The thermally conductive paste according to this embodiment can be used, for example, to form at least one of the thermally conductive layers 40, 60. Specifically, at least one of the thermally conductive layers 40, 60 can be formed by applying the thermally conductive paste and then heating and curing it. The thermally conductive paste according to this embodiment has an adhesive surface area of ​​2 cm2. 2 This thermal conductive paste is particularly suitable for use in cases where the adhesive surface area is 10 cm 2 In the above cases, and furthermore, the area of ​​the adhesive surface is 36 cm 2 It is preferably used in the above cases.

[0023] The thermal conductive paste contains a thermosetting resin and a filler having at least a part of its surface covered with a metal. Each component of the thermal conductive paste will be described below.

[0024] [Thermosetting resin] The thermosetting resin can be one or a combination of two or more selected from the following: epoxy resins; phenolic resins; resins having a triazine ring, such as urea resins and melamine resins; unsaturated polyester resins; maleimide resins, such as bismaleimide compounds; polyurethane resins; diallyl phthalate resins; silicone-based resins, benzoxazine resins, polyimide resins, polyamide-imide resins; and cyanate ester resins, such as benzocyclobutene resins, novolac-type cyanate resins, bisphenol A-type cyanate resins, bisphenol E-type phenolic resins, and tetramethylbisphenol F-type cyanate resins.

[0025] Specific examples of epoxy resins include bisphenol type epoxy resins such as bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol F type epoxy resins, tetramethyl bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol E type epoxy resins, bisphenol M type epoxy resins, bisphenol P type epoxy resins, and bisphenol Z type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; biphenyl type epoxy resins, biphenyl aralkyl type epoxy resins, aryl One or a combination of two or more selected from alkylene type epoxy resins, naphthalene type epoxy resins, anthracene type epoxy resins, phenoxy type epoxy resins, dicyclopentadiene type epoxy resins, norbornene type epoxy resins, adamantane type epoxy resins, fluorene type epoxy resins, trisphenylmethane type epoxy resins, and epoxy monomers such as 4-tert-butylphenyl glycidyl ether, m,p-cresyl glycidyl ether, phenyl glycidyl ether, cresyl glycidyl ether, and 1,4-cyclohexanedimethanol diglycidyl ether can be used.

[0026] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the content of the thermosetting resin is preferably 3 parts by mass or more, and more preferably 5 parts by mass or more. The upper limit of the content of the thermosetting resin is preferably 15 parts by mass or less, and more preferably 10 parts by mass or less. By keeping the content of the thermosetting resin within the above range, the hardening property of the thermal conductive paste is improved.

[0027] [Filler] The filler contained in the thermally conductive paste according to this embodiment is sintered by heat-treating the thermally conductive paste, forming a particle-connected structure. That is, in the adhesive layer obtained by heating the thermally conductive paste, adjacent fillers are fused to each other. This improves the thermal conductivity and adhesion to substrates, semiconductor elements, heat sinks, etc., of the adhesive layer obtained by heating the thermally conductive paste.

[0028] The filler according to the present embodiment includes both particles whose entire surface is made of metal and particles whose surface is at least partially coated with metal. Particles whose entire surface is coated with metal are, for example, coated silver powders containing resin particles such as silicone resin particles and silver covering the surfaces of the resin particles.

[0029] The above-mentioned coated silver powder is, for example, a particle (silicone resin particle) made of an organopolysiloxane obtained by polymerizing an organochlorosilane such as methylchlorosilane, trimethyltrichlorosilane, dimethyldichlorosilane, etc., coated with silver. Alternatively, the surface of a silicone resin particle made of a silicone resin having a basic skeleton formed by further three-dimensionally crosslinking the above-mentioned organopolysiloxane is coated with silver.

[0030] The shape of the filler is not particularly limited, but may be, for example, spherical, dendritic, string-like, flake-like, aggregated, polyhedral, etc. From the viewpoint of improving the sinterability of the filler and improving the uniformity of sintering, it is preferable that a spherical filler is included. Also, from the viewpoint of reducing costs, it is preferable that a flake-like filler is included.

[0031] The particle diameter D50 of the filler at 50% cumulative frequency in a volume-based cumulative frequency distribution curve measured using a laser diffraction particle size distribution analyzer is preferably 0.1 μm or more, more preferably 1.0 μm or more, and even more preferably 2.0 μm or more. The particle diameter D50 of the filler is preferably 10 μm or less, more preferably 9.0 μm or less, even more preferably 8.0 μm or less, particularly more preferably 7.0 μm or less, and most preferably 6.0 μm or less.

[0032] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the filler content is preferably 80 parts by mass or more, and more preferably 82 parts by mass or more, and the upper limit of the filler content is preferably 95 parts by mass or less, and more preferably 92 parts by mass or less.

[0033] [Hardening agent] The thermally conductive paste according to the present embodiment may further include a curing agent. For example, a phenol resin curing agent can be used as the curing agent. Specifically, the phenol resin curing agent may be one or a combination of two or more selected from the following: novolac-type phenol resins such as phenol novolac resin, cresol novolac resin, bisphenol A-type novolac resin, and triazine skeleton-containing phenol novolac resin; bisphenol compounds such as bisphenol A and bisphenol F (dihydroxydiphenylmethane); unmodified resol phenol resin; resol-type phenol resins such as oil-modified resol phenol resins modified with tung oil, linseed oil, and walnut oil; aralkyl-type phenol resins such as phenol aralkyl resin and biphenyl aralkyl-type phenol resin; and triphenylmethane-type phenol resin.

[0034] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the content of the hardener is preferably 0.5 parts by mass or more, and more preferably 0.7 parts by mass or more. The upper limit of the content of the hardener is preferably 2.0 parts by mass or less, and more preferably 1.5 parts by mass or less. By keeping the content of the hardener within the above range, the hardening property of the thermal conductive paste is improved.

[0035] [Cure accelerator] The thermally conductive paste according to the present embodiment may further include a curing accelerator for accelerating the reaction between the reactive group of the thermosetting resin and the reactive group of the curing agent. The curing accelerator may be one or a combination of two or more selected from the following: imidazole curing accelerators; phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines and tertiary amines such as dicyandiamide, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine; and nitrogen atom-containing compounds such as quaternary ammonium salts of the above amidines or tertiary amines.

[0036] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the content of the hardening accelerator is preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more. The upper limit of the content of the hardening accelerator is preferably 0.5 parts by mass or less, and more preferably 0.3 parts by mass or less. By setting the content of the hardening accelerator within the above range, the hardening property of the thermal conductive paste is improved.

[0037] [Acrylic Monomer] The thermal conductive paste according to this embodiment may further contain an acrylic monomer to improve heat resistance and impact resistance. As the acrylic monomer, a monofunctional acrylic monomer having only one (meth)acrylic group or a polyfunctional acrylic monomer having two or more (meth)acrylic groups may be used. Alternatively, an acrylic acid polymer such as UG-4035 manufactured by Toagosei Co., Ltd. may be used.

[0038] Examples of monofunctional acrylic monomers include 2-phenoxyethyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tridecyl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethylhexyl diethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and the like. p) acrylate, methoxydipropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, phenylphenol ethylene oxide modified (meth)acrylate, isobornyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate quaternized, glycidyl (meth)acrylate, neopentyl glycol (meth)acrylic acid benzoate, 1,One or a combination of two or more selected from 4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalic acid, 2-(meth)acryloyloxyethyl acid phosphate, and 2-(meth)acryloyloxyethyl acid phosphate can be used.

[0039] Of the above specific examples, it is preferable to use 2-phenoxyethyl methacrylate as the monofunctional acrylic monomer, as this can improve the adhesion of the thermal conductive paste.

[0040] Specific examples of polyfunctional acrylic monomers include ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, hexane-1,6-diol bis(2-methyl(meth)acrylate), 4,4'-isopropylidenediphenol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3,3,4,4,5,5-octadecyl acrylate, and the like. One or a combination of two or more selected from the group consisting of fluorohexane, 1,4-bis((meth)acryloyloxy)butane, 1,6-bis((meth)acryloyloxy)hexane, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, N,N'-(1,2-dihydroxyethylene)bis(meth)acrylamide, and 1,4-bis((meth)acryloyl)piperazine can be used.

[0041] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the content of the acrylic monomer is preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more. The upper limit of the content of the acrylic monomer is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less. By keeping the content of the acrylic monomer within the above range, the heat resistance and impact resistance of the thermal conductive paste are improved.

[0042] [Coupling agent] The thermal conductive paste according to the present embodiment may further contain a coupling agent. This can increase the fluidity of the thermal conductive paste. As the coupling agent, for example, a silane-based coupling agent, a titanium-based coupling agent, a zirconia-based coupling agent, an aluminum-based coupling agent, etc. can be used.

[0043] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the content of the coupling agent is preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more. The upper limit of the content of the coupling agent is preferably 1.0 parts by mass or less, and more preferably 0.5 parts by mass or less. By keeping the content of the coupling agent within the above range, the hardening property of the thermal conductive paste is improved.

[0044] [Adhesion aid] The thermally conductive paste according to the present embodiment may contain an adhesion aid, such as EH3636AS manufactured by ADEKA CORPORATION.

[0045] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the adhesion assistant content is preferably 0.005 parts by mass or more, and more preferably 0.01 parts by mass or more. The upper limit of the adhesion assistant content is preferably 0.5 parts by mass or less, and more preferably 0.3 parts by mass or less. By setting the adhesion assistant content within the above range, the hardening property of the thermal conductive paste is improved.

[0046] [Plasticizer] The thermally conductive paste according to the present embodiment may contain a plasticizer. For example, an allyl resin may be used as the plasticizer. More specifically, an allyl polymer such as an allyl ester resin obtained by reacting a dicarboxylic acid, an allyl alcohol, and a compound having an allyl group may be used. Specific examples of the dicarboxylic acid that can be used include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, phthalic acid, tetrahydrophthalic acid, and hexahydrophthalic acid. Specific examples of the compound having the allyl group include polyether, polyester, polycarbonate, polyacrylate, polymethacrylate, polybutadiene, and butadiene-acrylonitrile copolymer having an allyl group.

[0047] When the total amount of the thermally conductive paste is 100 parts by mass, the lower limit of the plasticizer content is preferably 0.5 parts by mass or more, and more preferably 1.0 parts by mass or more, and the upper limit of the plasticizer content is preferably 8.0 parts by mass or less, and more preferably 6.0 parts by mass or less.

[0048] [Initiator] The thermally conductive paste according to the present embodiment may contain an initiator. Examples of initiators that can be used include azo compounds and peroxides. Examples of peroxides that can be used include organic peroxides such as diacyl peroxides, dialkyl peroxides, and peroxyketals. More specifically, examples of peroxides that can be used include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane and 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane; hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide; di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, and 2,5-dimethyl-2 One or a combination of two or more selected from the following can be used: dialkyl peroxides such as 2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, and di-t-butyl peroxide; diacyl peroxides such as dibenzoyl peroxide and di(4-methylbenzoyl)peroxide; peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate; and peroxy esters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-hexyl peroxybenzoate, t-butyl peroxybenzoate, and t-butyl peroxy 2-ethylhexanoate.

[0049] When the total amount of the thermal conductive paste is 100 parts by mass, the lower limit of the content of the initiator is preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more, and the upper limit of the content of the initiator is preferably 1.0 parts by mass or less, and more preferably 0.5 parts by mass or less.

[0050] [solvent] The thermally conductive paste according to the present embodiment may contain a solvent. Examples of the solvent include methyl carbitol, ethyl carbitol, butyl carbitol, methyl carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, acetylacetone, methyl isobutyl ketone (MIBK), anone, diacetone alcohol, ethyl cellosolve, methyl cellosolve, butyl cellosolve, ethyl cellosolve acetate, methyl cellosolve acetate, butyl cellosolve acetate, ethyl alcohol, propyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, and γ-terpineol. Alcohols such as terpineol (a mixture of alpha, beta, and gamma), dihydroterpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol, or glycerin; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone (3,5,5-trimethyl-2 ketones such as ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl hexanoate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate or tripentyl phosphate;One or a combination of two or more selected from ethers such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane; ester ethers such as 2-(2-butoxyethoxy)ethane acetate; ether alcohols such as 2-(2-methoxyethoxy)ethanol, toluene, xylene, n-paraffin, isoparaffin, dodecylbenzene, turpentine oil, kerosene or light oil; nitriles such as acetonitrile or propionitrile; amides such as acetamide or N,N-dimethylformamide; low molecular weight volatile silicone oil, or volatile organic modified silicone oil, etc. may be used.

[0051] When the entire thermal conductive paste is taken as 100 parts by mass, the lower limit of the solvent content is preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more. The upper limit of the solvent content is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less. By keeping the solvent content below the upper limit, the cure shrinkage rate of the thermal conductive paste is reduced, and the adhesiveness is improved.

[0052] Next, the physical properties of the thermally conductive paste according to this embodiment will be described.

[0053] [Adhesion strength] The thermal conductive paste according to this embodiment has an adhesion strength measured under the following conditions of preferably 310 N or more, more preferably 330 N or more, even more preferably 350 N or more, and even more preferably 370 N or more. 2 In the above bonding, sufficient adhesion is obtained. [conditions] 1. Prepare a copper plate measuring 10 mm or more x 10 mm or more and an aluminum plate measuring 10 mm x 10 mm and 0.5 mm thick. 2.2mm 3 More than 5mm 3 The following thermally conductive paste is applied to the copper plate. 3. The aluminum plate is placed on the area of ​​the copper plate where the thermally conductive paste is applied, and the aluminum plate is pressed against the copper plate with a pressure of 50N or more and 100N or less. 4. The thermally conductive paste is hardened under the following conditions: heating temperature: 200°C, heating time: 120 minutes. 5. In accordance with JIS Z 3198-7, a load is applied using a die shear tester with a shear jig moving speed of 20 mm / min, and the maximum shear load is taken as the adhesion strength.

[0054] [Thermal Conductivity] The thermal conductive paste according to this embodiment has a thermal conductivity of 12 W / m K or more, and more preferably 15 W / m K or more, of a hardened body obtained by hardening under conditions of a heating temperature of 200°C and a heating time of 120 minutes. This improves the heat dissipation properties of the thermal conductive paste.

[0055] [Cure shrinkage rate] The cure shrinkage rate, measured under the following conditions in accordance with JIS K 6941, is preferably 15% or less, and more preferably 11% or less, which can suppress misalignment of components during the manufacture of a semiconductor device. [conditions] [Condition 2] The thermally conductive paste is applied onto a chip measuring 1.7 mm x 7 mm. 2. A 3 mm x 3 mm chip is mounted on the area where the thermally conductive paste is applied, and the thickness T1 of the thermally conductive paste at this time is measured. 3. The thermal conductive paste is cured by heating from 30°C to 200°C over 60 minutes, and then heated at 200°C for 120 minutes, and the thickness T2 of the cured thermal conductive paste is measured. 4. The value of {(T2-T1) / T1} x 100 is the curing shrinkage rate.

[0056] [Curing temperature] The thermally conductive paste according to this embodiment preferably has a curing temperature of, for example, 220° C. or less, more preferably 200° C. or less, and even more preferably 180° C. or less. By having the curing temperature be equal to or less than the above upper limit, the influence of heat on semiconductor elements and the like during the manufacturing process can be suppressed.

[0057] [Method of manufacturing thermal conductive paste] The thermal conductive paste according to the present embodiment is prepared, for example, by mixing the above-mentioned raw material components. A known method can be used for mixing, and for example, a three-roll mill or a mixer can be used. The mixture obtained may be further degassed. For example, the mixture may be left under vacuum to degas.

[0058] [Method of manufacturing semiconductor device] The semiconductor device according to this embodiment can be manufactured using the above-mentioned thermally conductive paste. The manufacturing method of the semiconductor device may include, for example, a step of placing the semiconductor element 20 on one side of the substrate 10 so that the other side faces the substrate 10, a step of applying a thermally conductive paste to the surface of one side of the semiconductor element 20 (opposite to the other side), a step of placing the heat spreader 30 so as to contact the thermally conductive paste and cover at least one side of the semiconductor element 20, a step of applying a thermally conductive paste to one side of the heat spreader 30 facing the heat sink 50, a step of placing the heat sink 50 on one side of the heat spreader 30, and a step of heating a structure including the substrate 10, the semiconductor element 20, the thermally conductive paste, the heat spreader 30, and the heat sink 50 to harden the thermally conductive paste, and bond the heat spreader 30 and the heat sink 50.

[0059] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.

[0061] [Thermal conductive paste] A varnish was obtained by mixing the ingredients of the first raw material according to the amounts shown in Table 1 below. The second raw material was added to the obtained varnish according to the amounts shown in Table 1 below, and kneaded at room temperature with a three-roll mill to produce a thermally conductive paste.

[0062] [Table 1]

[0063] The details of the raw material components in Table 1 are shown below. Note that the description of raw material components used only in the comparative examples is omitted. (1st raw material) Thermosetting resin: Bisphenol F type epoxy resin (Nippon Kayaku Co., Ltd., RE-303S) Hardener: Biphenol (Honshu Chemical Industry Co., Ltd., SBM-3901) Acrylic monomer: Ethylene glycol dimethacrylate (Kyoeisha Chemical Co., Ltd., Light Ester EG) Plasticizer: Allyl polymer (Kanto Chemical Co., Ltd., SBM-8C03) Adhesion aid: Dicyandiamide (ADEKA Corporation, EH3636AS) Coupling agent 1: 3-methacryloxypropylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-503P) Coupling agent 2: 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403E) Curing accelerator: 2-phenyl-1H-imidazole 4,5-dimethanol (Shikoku Kasei, 2PHZ-PW) Initiator: Dicumyl peroxide (Perkadox BC, manufactured by Nouryon Chemical Industries, Ltd.) Solvent 1: Tripropylene glycol mono n-butyl ether (Nippon Nyukazai Co., Ltd., BFTG) (Second raw material) Silver powder: flake silver powder, median diameter D50: 6.0 μm (Fukuda Metals, HKD-13A) Coated silver powder: (Mitsubishi Materials Corporation, SC1050-SSB) Coupling agent 4: 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBE-403) Solvent 2: Ethylene glycol mono-n-butyl ether acetate (Tokyo Chemical Industry Co., Ltd., SBM-8N01) Solvent 3: Tripropylene glycol mono n-butyl ether (Nippon Nyukazai Co., Ltd., BFTG)

[0064] [measurement] The thermally conductive pastes of the Examples and Comparative Examples were used to measure the following physical properties. The measurement results are shown in Table 1.

[0065] < Viscosity η5, Thixotropy η 0.5 / η5> At 25°C, a B-type viscometer was used to measure the viscosity η5 at a rotation speed of 5 rpm, and the viscosity η at a rotation speed of 0.5 rpm 0.5 And, η 0.5 The value of / η5 was calculated. Note that a BF viscometer (DV3T, manufactured by Brookfield) was used as the viscometer.

[0066] <Adhesion strength> The adhesion strength was measured under the following conditions. [conditions] 1. A copper plate measuring 10 mm x 10 mm and an aluminum plate measuring 10 mm x 10 mm and having a thickness of 0.5 mm were prepared. 2.2mm 3 A thermally conductive paste was applied to a copper plate. 3. The aluminum plate was placed on the area of ​​the copper plate where the thermally conductive paste had been applied, and the aluminum plate was pressed against the copper plate with a pressure of 100 N. 4. The thermally conductive paste was hardened under the following conditions: heating temperature: 200°C, heating time: 120 minutes. 5. In accordance with JIS Z 3198-7, a load was applied using a die shear tester at a shear jig moving speed of 20 mm / min, and the maximum shear load was taken as the adhesion strength.

[0067] <Elasticity modulus> The thermally conductive paste was applied to a 4 mm x 20 mm x 0.3 mm mold, heated from 30°C to 200°C over 60 minutes, and then heated at 200°C for 120 minutes to obtain a test piece. Using this test piece, the storage modulus (E') at 25°C was measured in accordance with JIS K 6911 using DMA (dynamic viscoelasticity measurement, SII Nanotechnology DMS6100, tensile mode) at a heating rate of 5°C / min and a frequency of 1 Hz.

[0068] <Glass transition temperature (Tg) and linear expansion coefficient> The thermally conductive paste was applied to a mold of 4 mm x 10 mm x 0.15 mm, and the temperature was raised from 30 ° C to 200 ° C over 60 minutes, and then heated at 200 ° C for 120 minutes to obtain a test piece. Next, using a thermomechanical analyzer (Seiko Instruments Inc. TMA / SS6100), the test piece was pulled with a constant load (10 mN) while the temperature was raised from -65 ° C at a heating rate of 5 ° C / min. The expansion amount of the test piece relative to the temperature of the test piece was detected as an electrical output by a differential transformer, and a graph was created showing the expansion amount of the test piece relative to the temperature of the test piece. Then, the glass transition temperature (Tg) was obtained from the inflection point of the above graph, and the linear expansion coefficient α1 at a temperature below the calculated glass transition temperature (Tg) and the linear expansion coefficient α2 at a temperature above the glass transition temperature (Tg) were obtained. Then, the value of α1 / α2 was calculated.

[0069] <Cure shrinkage rate> The cure shrinkage was measured under the following conditions in accordance with JIS K 6941. [conditions] The thermally conductive paste is applied onto a chip measuring 1.7 mm x 7 mm. 2. A 3 mm x 3 mm chip is mounted on the area where the thermally conductive paste is applied, and the thickness T1 of the thermally conductive paste at this time is measured. 3. The thermal conductive paste is cured by heating from 30°C to 200°C over 60 minutes, and then heated at 200°C for 120 minutes, and the thickness T2 of the cured thermal conductive paste is measured. 4. The value of {(T2-T1) / T1} x 100 is the curing shrinkage rate.

[0070] <Thermal conductivity> The thermally conductive paste was applied to a mold of 10 mm x 10 mm x 1.0 mm, and the temperature was raised from 30 ° C to 200 ° C over 60 minutes, and then heated at 200 ° C for 120 minutes to obtain a test piece. Next, the thermal diffusion coefficient (α) in the length direction of the plate-shaped test piece was measured by the laser flash method using a Xe flash analyzer TD-1RTV manufactured by ULVAC. The measurement was performed under the condition of 25 ° C in an air atmosphere. The thermal conductivity was calculated based on the following formula from the measured values ​​of the thermal diffusion coefficient (α), specific heat (Cp), and specific gravity (SP). (Formula): Thermal conductivity [W / m K]=α[m 2 / s]×Cp[J / kg K]×Sp[g / cm 3 ]

[0071] <Volume resistivity> The thermally conductive paste was applied to a 10 mm x 10 mm x 1.0 mm mold, heated from 30°C to 200°C over 60 minutes, and then heated at 200°C for 120 minutes to obtain a test piece. The volume resistivity of the surface of the cured product obtained was measured by a direct current four-electrode method using a milliohmmeter (manufactured by HIOKI Corporation) with electrodes spaced 40 mm apart.

[0072] [evaluation] The thermally conductive paste thus obtained was used to evaluate the adhesion of the thermally conductive paste by the following measurement method. [Measurement method] 1. A copper plate measuring 10 mm x 10 mm and an aluminum plate measuring 10 mm x 10 mm and having a thickness of 0.5 mm were prepared. 2.2mm 3 A thermally conductive paste was applied to a copper plate. 3. The aluminum plate was placed on the area of ​​the copper plate where the thermally conductive paste had been applied, and the aluminum plate was pressed against the copper plate with a pressure of 100 N. 4. The thermally conductive paste was hardened under the following conditions: heating temperature: 200°C, heating time: 120 minutes. 5. The hardened thermal conductive paste was heated to 150°C and held there for 30 minutes, then cooled to -40°C and held there for 30 minutes, which constituted one cycle. The number of cycles until the adhesive peeled off was measured.

[0073] The respective measurement results are shown in Table 1. As shown in Table 1, the thermally conductive paste according to Comparative Example 2 could only withstand about 500 cycles, and the thermally conductive paste according to Comparative Example 3 could only withstand about 100 cycles, whereas the thermally conductive paste according to the present embodiment could withstand more than 1000 cycles, and it was confirmed that it had excellent adhesion. Note that, for Comparative Example 1, the measurement could not be performed because the adhesion was insufficient. [Explanation of symbols]

[0074] 10 Substrate 20 Semiconductor elements 30 Heat spreader 40, 60 Thermally conductive layer 50 Heatsink 70 Underfill material

Claims

1. 2 cm 2 A thermally conductive paste used for bonding in the above area, The method includes the steps of: forming a particle having at least a portion of a surface thereof made of metal; forming a thermosetting resin; and forming a solvent; A thermally conductive paste having an adhesion strength of 310 N or more as measured under the following condition 1. [Condition 1] 1. Prepare a copper plate measuring 10 mm or more x 10 mm or more and an aluminum plate measuring 10 mm x 10 mm and 0.5 mm thick. 2.2mm 3 More than 5mm 3 The following thermally conductive paste is applied to the copper plate.

3. The aluminum plate is placed on the area of ​​the copper plate where the thermally conductive paste is applied, and the aluminum plate is pressed against the copper plate with a pressure of 50N to 100N.

4. The thermally conductive paste is hardened under the conditions of a heating temperature of 200° C. and a heating time of 120 minutes.

5. In accordance with JIS Z 3198-7, a load is applied using a die shear tester at a shear jig moving speed of 20 mm / min, and the maximum shear load is regarded as the adhesion strength.

2. The thermal conductivity of the cured body obtained by curing the thermal conductive paste under the conditions of a heating temperature of 200° C. and a heating time of 120 minutes is 12 W / m·K or more. The thermally conductive paste according to claim 1 .

3. The cure shrinkage rate measured under the following condition 2 is 15% or less. The thermally conductive paste according to claim 1 or 2. [Condition 2] The thermally conductive paste is applied onto a chip of 1.7 mm x 7 mm.

2. A chip of 3 mm×3 mm is mounted on the area where the thermally conductive paste is applied, and the thickness T1 of the thermally conductive paste at this time is measured.

3. The thermal conductive paste is cured by increasing the temperature from 30° C. to 200° C. over 60 minutes, and then heated at 200° C. for 120 minutes, and the thickness T2 of the cured thermal conductive paste is measured.

4. The value of {(T2-T1) / T1} x 100 is the cure shrinkage rate.

4. The content of the solvent is 5 parts by mass or less based on the entire thermal conductive paste. The thermally conductive paste according to claim 1 or 2.

5. The particles include resin particles and coated silver powder containing silver that covers the surfaces of the resin particles. The thermally conductive paste according to claim 1 or 2.

6. Further comprising an allyl ester resin, The thermally conductive paste according to claim 1 or 2.

7. Includes a heat spreader and a heat sink. A semiconductor device, wherein the heat spreader and the heat sink are bonded together by the thermally conductive paste according to claim 1 or 2.

8. A method for manufacturing a semiconductor device, comprising the step of bonding a heat spreader and a heat sink using the thermally conductive paste according to claim 1 or 2.

Citation Information

Patent Citations

  • Semiconductor package, method for manufacturing semiconductor package and thermally conductive composition used therefor

    WO2020189446A1